Clinical study on the serum carcinoembryonic antigen, CA 19-9, CA 50 and alpha-fetoprotein levels in patients with myelodysplastic syndromes. - Dalamaga, Maria; Karmaniolas, Konstantinos; Kontos, Fanourios; Migdalis, Ilias; Dionyssiou-Asteriou, Amalia (Leuk Lymphoma, 2006)
The present study aimed to determine the serum carcinoembryonic antigen (CEA), CA 19-9, CA 50 and alpha-fetoprotein (alpha-FP) levels between patients with myelodysplastic syndromes (MDS) at diagnosis and controls to clarify their potential clinical significance. A case-control investigation was conducted over a three year period, covering 95 MDS cases and 95 age- and gender-matched controls. Mean serum CEA levels were significantly higher (P = 0.0002) in MDS patients at diagnosis than in hospital controls. Adjusting for age, gender, tobacco consumption, serum CA 19-9, CA 50 and alpha-FP levels, there is statistically significant evidence that serum CEA values are associated with increased risk of MDS (odds ratio = 2.33, 95% confidence interval = 1.56 - 3.49). Six patients with MDS developed malignancies 4-9 months after the diagnosis of myelodysplasia. Serum CEA could be used as marker together with other important diagnostic tools for evaluating an underlying or developing malignancy in patients suffering from MDS.
Keywords: Adult; Aged; Aged, 80 and over; alpha-Fetoproteins; Antigens, Tumor-Associated, Carbohydrate; Biomarkers, Tumor; CA-19-9 Antigen; Carcinoembryonic antigen; Case-Control Studies; Female; Humans; Male; Middle Aged; Myelodysplastic Syndromes